2001
DOI: 10.1002/1521-4095(200103)13:5<355::aid-adma355>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Controlled Energy Transfer in Conjugated Molecular Thin Films

Abstract: In α‐sexithienyl (T6) molecular thin films the spectral features of photoluminescence can be correlated to precise structural topologies and the nature of photoluminescence can be controlled. AFM images show that the topological features of T6 films evolve progressively from 2D to 3D structures with film thickness. It is shown that coalescence between different domains results in photoluminescence spectra that are dominated by the aggregate emission. The Figure shows the photoluminescence spectra of submonolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…This would indicate that the molecules associate at the aromatic core. T6.2 also associates with silica that is typical for oligothiophenes . This association affects the packing of oligomers at the surface of SiO 2 transistor gate dielectrica.…”
Section: Resultsmentioning
confidence: 99%
“…This would indicate that the molecules associate at the aromatic core. T6.2 also associates with silica that is typical for oligothiophenes . This association affects the packing of oligomers at the surface of SiO 2 transistor gate dielectrica.…”
Section: Resultsmentioning
confidence: 99%
“…Muccini and coworkers demonstrated that the mechanism of energy transfer in a-sexithienyl is highly sensitive to the molecular environment. [53] Through comparing sub-mono-layer and lamellae architectures they were able to relate features seen in the photoluminescence spectra to precise structural topologies.…”
Section: Understanding Exciton Dynamicsmentioning
confidence: 99%
“…[2][3][4] There are many ways to produce nanostructured polymers including self-assembling method, Langmuir-Blodget technique, layer-by-layer technique, etc. [5][6][7] In recent years, environmentally-friendly reaction processes have been vigorously studied from the standpoint of green chemistry. Most recently, ionic liquids (IL)s have gained much attention as green reaction solvents for organic synthesis.…”
Section: Introductionmentioning
confidence: 99%